University’s Efforts In Addressing Climate Change Challenges : A Case at Raden Intan State Islamic University - Wan Jamaluddin; Suci Wulan Pawhestri; Aulia Ulmillah (Journal of Sustainability Perspectives, 2024)
Addressing climate change has become a top priority for universities worldwide. This paper examines Raden Intan State Islamic University’s initiatives to confront climate change through its Eco-Campus program. In Indonesia, a country highly vulnerable to climate change, UIN Raden Intan Lampung recognizes its responsibility in promoting sustainability and reducing environmental impacts. Using a qualitative approach, this case study explores the university's comprehensive strategies, which include institutional policies and grassroots efforts. The campus focuses on reducing carbon emissions, adopting renewable energy, and enhancing climate resilience. Key initiatives include maintaining large green spaces that lower temperatures and absorb carbon dioxide, using energy-saving devices like LED lights, and installing solar panels to minimize the carbon footprint. In waste management, the university turns organic waste into compost and repurposes food waste to feed larvae, which are then processed into animal feed. Water conservation efforts are supported by artificial ponds, ensuring a reliable water supply and maintaining greenery during dry seasons. The university also promotes sustainable transportation by encouraging bicycle use and limiting vehicle parking to reduce emissions. Overall, UIN Raden Intan Lampung exemplifies how a university can integrate sustainability into campus life, serving as a model for climate change mitigation efforts.